1989
DOI: 10.2337/diab.38.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Atherosclerosis-Like Lesions Induced by Hyperinsulinism in Wistar Rats

Abstract: To elucidate the possible role of hyperinsulinism in the etiology of diabetic macroangiopathy, we studied the long-term effects of insulin injection on the arterial wall of the rat both biochemically and histologically. Fifty male Wistar rats were divided into two groups. One group was subjected to daily injection of insulin-zinc suspension (20 U/kg), and the other group was treated with saline. After 1 yr, all the animals were killed, and the lipid contents in the intimal media of their aortas were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…1 Moreover, atherosclerosis-like lesions were documented when long-term insulin injections were performed in rats. 26 In addition, the intensive treatment of diabetes with insulin was not associated with a reduction in the occurrence of coronary artery disease in either the DCCT trial 27 or the UKPDS Study. 28 In many NIDDM patients, insulin levels are higher than those in nondiabetic subjects.…”
Section: Role Of Hyperinsulinemia On Vsmcs In Vitro and On Neointimalmentioning
confidence: 98%
“…1 Moreover, atherosclerosis-like lesions were documented when long-term insulin injections were performed in rats. 26 In addition, the intensive treatment of diabetes with insulin was not associated with a reduction in the occurrence of coronary artery disease in either the DCCT trial 27 or the UKPDS Study. 28 In many NIDDM patients, insulin levels are higher than those in nondiabetic subjects.…”
Section: Role Of Hyperinsulinemia On Vsmcs In Vitro and On Neointimalmentioning
confidence: 98%
“…The theoretical drawback of treating type 2 diabetes with exogenous insulin, based on its property as a potent growth‐factor which might result in increased muscularity of the arterial wall [60], did not translate into increased risk of a cardiovascular event or mortality in the UKPDS [39]. However, neither is there substantive evidence that long‐term insulin therapy reduces these outcomes in patients with type 2 diabetes, even though life‐saving benefits have been reported for insulin infusions to address hyperglycaemia in critically ill patients [61] and, when followed by intensive subcutaneous insulin therapy, to reduce 1‐year mortality after an MI in patients with diabetes [62].…”
Section: The Effects Of ‘Older Generation’ Antihyperglycaemic Drugs Omentioning
confidence: 99%
“…Unfortunately, only few studies have investigated pro‐atherosclerotic effects of exogenous insulin using animal models. In non‐diabetic animal models, it has been shown that long‐term insulin injections increased aortic lipid content with subsequent increased intima thickening [60,61], whereas oral insulin administration and euglycaemic/hyperinsulinaemic infusion decreased atherosclerotic lesion size [62,63]. In diabetic dogs, daily insulin infusion into femoral arteries increased artery tissue cholesterol and fatty acid content, suggesting a detrimental role for insulin in atherosclerosis during insulin resistance [64].…”
Section: Pro‐atherogenic Effects Of Insulinmentioning
confidence: 99%